2015
DOI: 10.1016/j.jad.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Baseline cognitive function does not predict the treatment outcome of electroconvulsive therapy (ECT) in late-life depression

Abstract: How well patients perform on neuropsychological tests at baseline is most likely not a predictor of, or otherwise not significantly associated with the treatment outcome of formula-based ECT in elderly patients with MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…The only difference was found in the general cognitive performance at baseline – excluded patients who performed worse according to MMSE scale. Nevertheless, analysing the available literature on the possible impact of cognitive impairment on ECT, it seems that this variable does not affect the effectiveness or tolerability of ECT treatment 8,39,53,54 . The study by Hausner et al 53 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only difference was found in the general cognitive performance at baseline – excluded patients who performed worse according to MMSE scale. Nevertheless, analysing the available literature on the possible impact of cognitive impairment on ECT, it seems that this variable does not affect the effectiveness or tolerability of ECT treatment 8,39,53,54 . The study by Hausner et al 53 .…”
Section: Discussionmentioning
confidence: 99%
“…6,7 It has also been shown that coexisting cognitive impairments do not affect the effectiveness of ECT. 8 ECT treatments also do not increase the risk of dementia in older patients treated with this method. 9 However, the controversy of ECT for many years now concerns not the efficacy, but the safety and tolerability.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Electroconvulsive therapy (ECT) can be an effective course of action, and the presence of cognitive impairment should not preclude its use. A study examining this issue found that baseline cognitive scores were not a predictor of ECT outcomes for elderly people with unipolar or bipolar depression (Bjolseth 2015).…”
Section: How We Might Manage Itmentioning
confidence: 99%